Specific PCR assays to determine bovine, porcine, fish and plant origin of gelatin capsules of dietary supplements. (15th November 2016) - Lee, Jae-Hwang; Kim, Mi-Ra; Jo, Cheon-Ho; Jung, Yoo-Kyung; Kwon, Kisung; Kang, Tae Sun
Highlights: Species-specific and universal primers were developed for 4 major gelatin materials. Limitations of qualitative testing of highly-processed gelatin were overcome. Sensitive and reliable PCR was developed to assess the origin of gelatin capsules. Abstract: Gelatin, a purified protein derived mostly from pig skin and bovine tissue, is used widely in both food and pharmaceutical industries. Here, to determine the species of origin of capsule gelatin, we developed a sensitive and reliable test using the polymerase chain reaction (PCR) method, which included 1) species-specific or universal primer sets, designed to detect short 16S ribosomal RNA (rRNA) gene sequences from cow, pig, and fish (tilapia) as well as genes encoding the large subunit of plant ribulose-1, 5-bisphosphate carboxylase oxygenase and 2) species-specific PCR coupled with whole-genome amplification. This method was used to verify manufacturing label claims of 28 gelatin capsule samples sold as dietary supplements. The results from 27 samples were consistent with gelatin-related information on the manufacturer label, while one sample that mentioned tilapia gelatin was found to contain only bovine DNA. This rapid method can therefore be used to verify the authenticity of gelatin capsules.